Stress Distribution Due to Loading on Premolar Teeth Implant: A Three Dimensional Finite Element Analysis - Hisam, M.; Lim, J.; Kurniawan, Denni; Nor, F. (2015)
© 2015 This study investigates, with the use of three dimensional finite element analysis, the stress that occurred on peri-implant bone during loading on a premolar implant. The bone was assumed to be transversely isotropic. The refined method is implemented in a case study, in which osseointegrated (25-100%) peri-implant premolar bone types II, III and IV with an implant attached is loaded with a 100 MPa load. The results showed that the less dense bone must support higher stress and strain, especially at the cortical region. Higher degree of osseointegration caused higher stress but lower strain. Both the bone type and the osseointegration condition significantly affect the stress-strain relation. For minimum stress and strain, denser and more osseointegrated peri-implant bone is desirable.